Extractives Content and Shrinkage of Nangka (Arthocarpus heteroohyllus) and Mangium (Acacia mangium) Woods - Deded S Nawawi; Satriyo H Wicaksono; Istie S Rahayu (Jurnal Ilmu dan Teknologi Kayu Tropis, 2013)
Extractives may contribute to dimensional stability of wood, physically and chemically, due to its heterogeneous of compounds. The objective of this research was to determine the extractives content of nangka (Arthocarpus heterophyllus) and mangium (Acacia mangium) woods and its influence on wood shrinkage. Extraction of wood was carried out by sokhlet method of ethanol and ethanol:benzene (1:2) for 12 h, and hot water for 3 h, respectively. The tangential, radial, and longitudinal shrinkage both of extracted and fresh wood samples were compared. The removal of ethanol, ethanol:benzene (1:2), and hot water soluble extractives increased tangential and radial shrinkage of wood, indicating that wood extractives was a significant factor influencing dimensional stability of wood. Extractive may influenced wood shrinkage physically as a bulking agent, and chemically by its contribution to hygroscopic properties of wood. However, longitudinal shrinkage of wood was not affected by extractives content which was, probably, due to very small of wood shrinkage in longitudinal direction. In addition, the basic density of wood was not affected by extractives content.Key words: Acacia mangium, Arthocarpus heterophyllus, bulking agent, extractives, wood shrinkage